The Word Formation Process in BBC News on the Invasion of Russia-Ukraine - Erlindawaty, Erlindawaty; Humairah, Ami (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2023)
This research aimed to identify the types of word formation processes used in four BBC News online articles on the issue of the invasion of Russia-Ukraine and to find out how those word formation processes occurred in each of the articles. This study employs the qualitative descriptive method, and the data is analyzed and classified in accordance with George Yule's (2020) theory. The researcher discovered 250 data on the word formation process in the articles. Borrowing with 0,8% of 2 data, compounding with 25,2% of 63 data, clipping with 0,8% of 2 data, conversion with 3,2% of 8 data, derivation with 68,8% of 172 data, and multiple processes with 1,2% of 3 data. Derivation is the most common type of word formation process found in the articles, while borrowing and clipping are the least common. From the seven types of word formation processes, coinage is the only one that is not found in articles